2001
DOI: 10.2466/pms.92.2.348-348
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Low Back Pain and Depression in a Sample of Veterans

Abstract: The relationship between chronic low back pain and scores on depression was examined in a sample of 31 veterans who completed a depression inventory. Analysis indicated that those with chronic low back pain scored significantly higher on depression than those without.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Depressive symptoms occur commonly in older persons, 8–10 are potentially modifiable, 11 and have been strongly associated with back pain in cross‐sectional studies of community‐dwelling persons 12–15 . Although it is widely recognized that chronic pain conditions can increase the risk for depressive symptoms, 16,17 at least two prospective studies of younger and middle‐aged persons found that the presence of depressive symptoms in those free of back pain at baseline predicted the onset of back pain over time 18,19 .…”
mentioning
confidence: 99%
“…Depressive symptoms occur commonly in older persons, 8–10 are potentially modifiable, 11 and have been strongly associated with back pain in cross‐sectional studies of community‐dwelling persons 12–15 . Although it is widely recognized that chronic pain conditions can increase the risk for depressive symptoms, 16,17 at least two prospective studies of younger and middle‐aged persons found that the presence of depressive symptoms in those free of back pain at baseline predicted the onset of back pain over time 18,19 .…”
mentioning
confidence: 99%